The mythology of work : how capitalism persists despite itself - Fleming, P. (Peter), 1972- (Pluto Press, 2015)
There was once a time when 'work' was inextricably linked to survival. But what was once an integral part of life has slowly morphed into a painful and meaningless routine, colonising almost every part of our lives. As our society is transformed into a factory that never sleeps, work becomes a universal reference point for everything else, devoid of moral or social worth. Blending theory with accounts of job-related suicides, office-induced paranoia, fear of relaxation, managerial sadism and cynical corporate social responsibility campaigns, Fleming provides a damning report on the way work consumes our lives in modern capitalist society. -- from back cover.